KOHESI LEKSIKAL DALAM KUMPULAN PUISI GELAP BERLAPIS-LAPIS - Rosyida Ekawati (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2014)
Poetry is one genre of literature. Literature in general is an art formthat is embodied through a language. A poem can be analyzed from the point of the structure and style of language features, the functions of language, structure and semantic context in all the linguistic frameworks. Through the analysis of lexical cohesion, it is expected to facilitate the reader to comprehend the text as a whole and objectively that lead no multi-interpretations.Analysis of lexical cohesion analysis in a collection of poems Gelap Berlapis-Lapis contain of repetition; repetition of words, phrases or rhythmic repetition. For analysis of synonymy, it consists of absolute and non-absolute synonymy. Meanwhile, aside from the existence of repetition and synonymy, there are also antonymy, hiponymy with its superordinate, metonymy and collocation . From the data analysis, lexical cohesion devices can tie each line into one whole cohesive poem and ease the readers to appreciate the poem through thereferences indicated by the lexical cohesion devices.